Therapeutic effects of the Qingre-Qushi recipe on atopic dermatitis through the regulation of gut microbiota and skin inflammation - Fang Shen; Chunjie Gao; Mingxia Wang; Xiaojie Ding; Hang Zhao; Mi Zhou; Jingyi Mao; Le Kuai; Bin Li; Dongming Wang; Huimin Zhang; Xin Ma (Heliyon, 2024)
Accumulating evidence has highlighted a strong association between gut microbiota and the occurrence, development, prevention, and treatment of atopic dermatitis (AD). The regulation of gut microbial dysbiosis by oral traditional Chinese medicine (TCM) has garnered significant attention. In the treatment of AD, the TCM formula Qingre-Qushi Recipe (QRQS) has demonstrated clinical efficacy. However, both the therapeutic mechanisms of QRQS and its impact on gut microbiota remain unclear. Thus, our study aimed to assess the efficacy of QRQS and evaluate its influence on the composition and diversity of gut microbiota in AD animal models. First, we investigated the therapeutic effect of QRQS on AD using two animal models: filaggrin-deficient mice (Flaky tail, ft/ft) and MC903-induced AD-like mice. Subsequently, we explored its influence on the composition and diversity of gut microbiota. Our results demonstrated that QRQS treatment ameliorated the symptoms in both ft/ft mice and MC903-induced AD-like mice. It also reduced the levels of serum IgE and pro-inflammatory cytokines, including IL-1β, IL-4, IL-5, IL-9, IL-13, IL-17A, and TNF-α. Furthermore, QRQS remarkably regulated gut microbiota diversity by increasing Lactobacillaceae and decreasing Bacteroidales. The inflammatory factors in peripheral serum of ft/ft mice showed a close correlation with gut microbiota, as determined using the Spearman correlation coefficient. Additionally, PICRUSt analysis revealed an enrichment in ascorbate and aldarate metabolism, fatty acid metabolism and biosynthesis, and propanoate metabolism in the QRQS group compared to the ft/ft group. Finally, we identified liquiritin as the primary active ingredient of QRQS using ultra-high-performance liquid chromatography-high-resolution mass spectrometry (UPLC-HRMS). Our findings revealed that QRQS improved AD-like symptoms and alleviated skin inflammation in ft/ft and MC903-induced mice. This suggests that modulating the gut microbiota may help elucidate its anti-inflammation activation mechanism, highlighting a new therapeutic strategy that targets the intestinal flora to prevent and treat AD.